The issue of legal status of Caspian and methods of establishing framework for legal distribution - Gaziyev, Farrukh (Riga Graduate School of Law, 2020)
This thesis is an in-depth study of the methods that can be used to divide the Caspian Basin in a fair manner under the international law. In these studies, the issue is analyzed from different perspectives and an in-depth analysis of division methods, agreements on the legal status of the Caspian Basin and UNCLOS, which plays an important role in international maritime law, has also been conducted.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Maritime law; Caspian sea